Pembinaan Aqidah Santri di Pesantren Al-Hamidiyah Sionggoton Kecamata Simangambat Kabupaten Padang Lawas Utara - Syafiah Hasibuan (Medan Resource Center, 2021)
This study seeks to examine and understand the development of the aqidah of students at the Al-Hamidiyah Islamic Boarding School Sionggoton. Aqidah is a belief that is firmly concluded in the heart, is binding and contains an agreement. In Islamic teachings, aqidah has a very important position if it is likened to a building, aqidah is the foundation. The sources of Islamic aqeedah are the Qur'an and the sunnah. The method used in this study is a qualitative method by describing the facts of the field as obtained from observations, documentation, and interviews (interviews). This type of research includes field research (Field Research) and library research (Library Research). Field research (Field Research) is to describe and describe the situation and phenomena more clearly regarding the situation. This research was conducted at the Al-Hamidiyah Islamic Boarding School Sionggon, Simangambat District, North Padang Lawas Regency.